Addressing Stereotype Threat is Critical to Diversity and Inclusion in Organizational Psychology - Casad, Bettina J.; Bryant, William J. (Frontiers in Psychology, 2016)
Recently researchers have debated the relevance of stereotype threat to the workplace. Critics have argued that stereotype threat is not relevant in high stakes testing such as in personnel selection. We and others argue that stereotype threat is highly relevant in personnel selection, but our review focused on underexplored areas including effects of stereotype threat beyond test performance and the application of brief, low-cost interventions in the workplace. Relevant to the workplace, stereotype threat can reduce domain identification, job engagement, career aspirations, and receptivity to feedback. Stereotype threat has consequences in other relevant domains including leadership, entrepreneurship, negotiations, and competitiveness. Several institutional and individual level intervention strategies that have been field-tested and are easy to implement show promise for practitioners including: addressing environmental cues, valuing diversity, wise feedback, organizational mindsets, reattribution training, reframing the task, values-affirmation, utility-value, belonging, communal goal affordances, interdependent worldviews, and teaching about stereotype threat. This review integrates criticisms and evidence into one accessible source for practitioners and provides recommendations for implementing effective, low-cost interventions in the workplace.